Optimal asset allocation under quadratic loss aversion - Ines Fortin; Jaroslava Hlouskova (Institute for Advanced Studies (IHS), 2012)
We study the asset allocation of a quadratic loss-averse (QLA) investor and derive conditions under which the QLA problem is equivalent to the mean-variance (MV) and conditional value-at-risk (CVaR) problems. Then we solve analytically the two-asset problem of the QLA investor for a risk-free and a risky asset. We find that the optimal QLA investment in the risky asset is finite, strictly positive and is minimal with respect to the reference point for a value strictly larger than the risk-free rate. Finally, we implement the trading strategy of a QLA investor who reallocates her portfolio on a monthly basis using 13 EU and US assets. We find that QLA portfolios (mostly) outperform MV and CVaR portfolios and that incorporating a conservative dynamic update of the QLA parameters improves the performance of QLA portfolios. Compared with linear loss-averse portfolios, QLA portfolios display significantly less risk but they also yield lower returns.
Keywords: D03; D81; G11; G15; G24; 330; quadratic loss aversion; prospect theory; portfolio optimization; MV and CVaR portfolios; investment strategy